APLIKASI MOBAJI: MENINGKATKAN PERTUMBUHAN TANAMAN DAN PENGENDALIAN HAMA PENGGEREK BATANG PADI - Aulia, Desi; Ariswanto, Joko; Setiyorini, Yekti Agus; Nisa’, Choirun; Siswanto, Joko (Program Kreativitas Mahasiswa - Penelitian, 2014)
One of the important pest in rice plants that triggers production declining of rice is rice yellow stem borer (Scircophaga incertulas) that can lead to crop yield failure. This pest attacks on the generative stage of rice plants and known as âbelukâ. MoBaJi is the mixture of MOL (local microorganism), onion extract and neem seed extract which serves as a botanical pesticide and as growth acceselerator of rice plants. The experiment was conducted in the laboratory of plant protection and FP-UBâs greenhouse. The research was conducted from February to June 2014. Randomized block design (RBD) was used for this research. This research contained 6 treatments with 3 replications with different concentration in each replication, and the treatments were repeated 3 times. The observations carried out up to 90 DAT of MoBaJi with scoring method. The variables of observations included plant height, tiller number, leaf number and intensity of pest attact. The results showed that MoBaJiâs treatment provided the highest influence on the mean of plant height that reached 64.71 cm (control: 51.45 cm), increase theÂ  tillers number (4 tillers compared to 2.8 tillers in control). The mean number of leaves in MoBaJi tratment were 26 strands (19 strands in control). The observation of pest attack intencity on the field showed that there were no visible pest attack in MoBaJiâs treatment. This results was confirmed by testing on a petridish of pests (early instars yellow rice stem borer larvae) and non-target insects (crickets). MoBaJiâs treatment was able to kill pests up to 90-100% within 4 hours without killing non-target insects, in contrast to chemical pesticides that killed both pests and non-target insects.Keywords: Â Rice, rice yellow stem borer, MoBaJi